Turkey : Sixth Review and Inflation Consultation Under the Stand-By Arrangement and Request for Waiver of Nonobservance and Applicability of Performance Criteria; Staff Report; Staff Supplement; and Press Release on the Executive Board Discussion. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2007)
The staff report for the Sixth Review and Inflation Consultation Under the Stand-By Arrangement on Turkey explains the macroeconomic framework and monetary and exchange rate policies. High interest rates, slowing credit growth, and election-related uncertainty were expected to weigh on private domestic demand and keep growth near its estimated long-term potential of 5 percent. The central bank renewed its commitment to building international reserves for prudential reasons. There was broad agreement on the need to ease labor regulations and taxes as fiscal resources permit.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet